Variability in pyrolysis product yield from novel shrub willow genotypes. (January 2015) - Serapiglia, Michelle J.; Mullen, Charles A.; Smart, Lawrence B.; Boateng, Akwasi A.
Abstract: Fast pyrolysis is becoming a more attractive conversion option for the production of biofuels, due to the potential for directly producing hydrocarbon fuels seamlessly compatible with petroleum products (drop-in fuels). Dedicated bioenergy crops, like perennial grasses and short-rotation woody crops, will be among the major sources of biomass for fast pyrolysis. To aid in the advancement of fast pyrolysis conversion and to identify appropriate feedstock crops, novel genotypes of shrub willow recently bred for high yield were evaluated for pyrolysis product yield using pyrolysis-gas chromatography-mass spectroscopy (py-GC/MS). The goal of this study was to understand how variations in biomass composition impact pyrolysis conversion efficiency and pyrolysis oil (bio-oil) quality by analyzing the composition of the pyrolysis vapors by py-GC/MS. The results of the py-GC/MS analysis showed significant differences in products from both non-catalytic and catalytic pyrolysis carried out over zeolite catalyst (HZSM-5), which were correlated with differences in biomass composition. For non-catalytic conversion, the most significant relationships were between the syringyl:guaiacyl (S:G) ratio in the biomass and phenolic monomers, in addition to levoglucosan yields and cellulose content. Production of phenols, guaiacols, and syringols were largely independent of total lignin content, but were strongly related to the S:G ratio. Willow genotypes with low ash content and high cellulose content produced more liquid products and higher levels of deoxygenated aromatics following catalytic pyrolysis. These results demonstrate that it is possible to breed for improvements in biomass compositional traits that can ultimately lead to improvements in bio-oil yield and quality. Highlights: Variations in willow biomass composition impact pyrolysis conversion and pyrolysis oil quality. Differences in pyrolysis products were correlated with differences in biomass composition. Production of phenols, guaiacols, and syringols were largely dependent on the S:G ratio. Breeding for improvements in biomass composition can lead to better bio-oil quality and yield.